PENGEMBANGAN MEDIA VIDEO ANIMASI POWTOON UNTUK PEMBELAJARAN PENDIDIKAN PANCASILA ELEMEN NKRI DI KELAS V SEKOLAH DASAR - Ocfa Chanda SP, Ryan; Reinita; Desyandri; Shilfia Iraqi, Hana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education instruction in elementary schools—specifically regarding the Unitary State of the Republic of Indonesia (NKRI) element—often relies on conventional media, which fails to adequately foster student engagement and learning motivation. This study aimed to develop a Powtoon-based animated video medium covering the topic